On the Non-existence of English "Prepositions" and "Complementisers" - Atiega, Awasha (Technium Social Sciences Journal, 2021)
The categories Preposition and Complementiser are distinctive in the literature and several diagnostic criteria have been put forward to identify the two categories in question. However, their existence was called into question and the current investigation showed that the distinction normally drawn between these two classes did not seem to work. That is, previous researchers including traditional grammarians seem to take those two-word classes for granted as the criteria set to define and distinguish them were problematic and did not succeed in defining them. The behaviour of most of the many items classified as prepositions and/or complementisers in some major grammars of English were tested with regard to a range of syntactic factors. On the basis of this, at least 59 distinct classes were formed and finally possible taxonomies of these 59 categories were also structured.